Marrow adipocytes inhibit the differentiation of mesenchymal stem cells into osteoblasts via suppressing BMP-signaling. Issue 1 (December 2017) - Abdallah, Basem
Abstract Background Reduced bone formation is associated with increased bone marrow fat in many bone-loss related diseases including aging, post-menopause, and anorexia nervosa. Several lines of evidence suggested the regulation of osteogenesis and adipogenesis of the bone marrow-derived mesenchymal (skeletal) stem cells (BMSCs) by paracrine mediators. This study aimed to investigate the impact of adipocytes-secreted factors on the cell proliferation and osteoblast differentiation of BMSCs. Methods Serum free conditioned medium (CM-Adipo) was collected from stromal ST2 cells-derived adipocytes. Cell viability, quantitative alkaline phosphatase (ALP) activity assay, Alizarin red staining for matrix mineralization and osteogenic gene array expression were performed to determine the effect of CM-Adipo on cell proliferation and osteoblast differentiation of primary murine BMSCs (mBMSCs). Regulation of BMPs and NF-κB signaling pathways by CM-Adipo were detected by Western blot analysis and gene reporter assay. Results CM-Adipo showed no effect on cell viability/proliferation of primary mBMSCs as compared to CM-control. On the other hand, CM-Adipo significantly inhibited the commitment of mBMSCs into osteoblastic cell lineage in dose-dependent manner. CM-Adipo was found to dramatically inhibit the BMP2-induced osteoblast differentiation and to activate the inflammatory NF-κB signaling in mBMSCs. Interestingly, treatment of mBMSCs with the selective inhibitor of NF-κB pathway, BAY11-770682, showed to retrieve the inhibitory effect of CM-Adipo on BMP2-induced osteoblast differentiation in mBMSCs. Conclusions Our data demonstrated that the marrow adipocytes exert paracrine inhibitory effect on the osteoblast differentiation of mBMSCs by blocking BMPs signaling in a mechanism mediated by adipokines-induced NF-κB pathway activation.